Pulse oximetry waveform: A non-invasive physiological predictor for the return of spontaneous circulation in cardiac arrest patients ---- A multicenter, prospective observational study. (December 2021) - Xu, Jun; Li, Chen; Tang, Hanqi; Tan, Dingyu; Fu, Yangyang; Zong, Liang; Jing, Daoyuan; Ding, Banghan; Cao, Yu; Lu, Zhongqiu; Tian, Yingping; Chai, Yanfen; et al.
Abstract: Objective: This study aimed to investigate the predictive value of pulse oximetry plethysmography (POP) for the return of spontaneous circulation (ROSC) in cardiac arrest (CA) patients. Methods: This was a multicenter, observational, prospective cohort study of patients hospitalized with cardiac arrest at 14 teaching hospitals cross China from December 2013 through November 2014. The study endpoint was ROSC, defined as the restoration of a palpable pulse and an autonomous cardiac rhythm lasting for at least 20 minutes after the completion or cessation of CPR. Results: 150 out-of-hospital cardiac arrest (OHCA) patients and 291 in-hospital cardiac arrest (IHCA) patients were enrolled prospectively. ROSC was achieved in 20 (13.3%) and 64 (22.0%) patients in these cohorts, respectively. In patients with complete end-tidal carbon dioxide (ETCO2 ) and POP data, patients with ROSC had significantly higher levels of POP area under the curve (AUCp), wave amplitude (Amp) and ETCO2 level during CPR than those without ROSC (all p  < 0.05). Pairwise comparison of receiver operating characteristic (ROC) curve analysis indicated no significant difference was observed between ETCO2 and Amp (p = 0.204) or AUCp (p = 0.588) during the first two minutes of resuscitation. Conclusion: POP may be a novel and effective method for predicting ROSC during resuscitation, with a prognostic value similar to ETCO2 at early stage.